PENINGKATAN HASIL BELAJAR SISWA KELAS XI MIPA 2 SMAN 1 TIDORE KEPULAUAN MELALUI PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW - Masri Kasim (Universitas Khairun, 2020)
The application of a varied learning model needs to be done by the teacher to improve student learning outcomes. Jigsaw Cooperative Learning allows students to be actively involved in the learning process so that it has a positive impact on the quality of interaction and communication among students. The method used in this research is a quasi experiment. Data obtained through actions to fix problems in the learning process with a cycle consisting of 4 stages. The results showed that student learning outcomes increased, marked by increased student attention in listening to teacher directions, a responsible attitude emerged and worked together in working on group assignments. Communication between groups is well established, students work on group assignments creatively, students help each other, and give opinions to other groups. Students also learn to respect and appreciate the opinions of others and the emergence of a spirit of leadership in students. In addition, student learning outcomes also increase with the use of multi-methods and learning media, as well as different study room designs for each action, so as to create a conducive and enjoyable learning atmosphere for students.